1999
DOI: 10.1590/1807-1929/agriambi.v3n1p11-17
|View full text |Cite
|
Sign up to set email alerts
|

Composição Química De Águas Do Cristalino Do Nordeste Brasileiro

Abstract: RESUMOObjetivando-se determinar a variação da composição iônica de águas do cristalino do Nordeste brasileiro, realizou-se este trabalho utilizando-se um banco de dados correspondente a 557 resultados de análises químicas de água de diversas fontes, com condutividade elétrica (CEa) até 5.000 µS cm ABSTRACTThe objective of present study was to evaluate variation of ionic composition of water from cristalline region of the northeast Brazil, utilising data bank of 557 results of chemical analysis, with electrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 1 publication
1
15
0
16
Order By: Relevance
“…Other studies on salinization of groundwaters by evaporation (Schoeller, 1959;Cruz & Melo, 1968;Silva Júnior et al, 1999;Lopes, 2008) corroborate these results, which are consistent with the study of Robaux (1953) for arid zones, who found that direct evaporation acts up to 2 m deep, but considers that it can reach 22 m in alluvial soils, through the influence of capillarity, promoting a progressive salt concentration.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Other studies on salinization of groundwaters by evaporation (Schoeller, 1959;Cruz & Melo, 1968;Silva Júnior et al, 1999;Lopes, 2008) corroborate these results, which are consistent with the study of Robaux (1953) for arid zones, who found that direct evaporation acts up to 2 m deep, but considers that it can reach 22 m in alluvial soils, through the influence of capillarity, promoting a progressive salt concentration.…”
Section: Resultssupporting
confidence: 84%
“…Water with high salt concentration is usually found in areas of crystalline rock formation (Silva Júnior et al, 1999;Lopes et al, 2008), while water with low salt concentration is found in areas of sedimentary rocks (Andrade Júnior et al, 2006;Silva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Esse comportamento de diluição dos sais no período chuvoso é comum nas regiões semiáridas, pois as águas das chuvas possuem uma concentração salina de CE 0,05d Sm -1 . Os principais elementos responsáveis por essa tendência na região semiárida são os Na + , Cl - (SILVA JÚNIOR et al, 1999 3-e SO 4 -, são maiores no grupo 4, que corresponde ao período chuvoso, época em que a chuva, ao promover a lavagem dos solos, carreia para os corpos hídricos os elementos provenientes da atividade humana. Uma outra possível fonte para esses íons estarem presentes são os adubos aplicados nos perímetros irrigados, que utilizam principalmente uréia, nitrato de potássio, cloreto de potássio e superfosfato como fonte de macro nutrientes para culturas como coco e banana (D'ALMEIDA et al, 2005).…”
Section: Resultsunclassified
“…Further, water sources with high salt concentrations are quite common (SILVA et al, 2005;BEZERRA et al, 2010). Silva Júnior et al (1999 evaluated the variation in the ionic composition of water from the crystalline region in the Northeast of Brazil (the states of Paraíba, Rio Grande do Norte, and Ceará) and observed a predominance of sodium-chloride water with certain variation regardless of the salinity level, site, or source.…”
Section: Introductionmentioning
confidence: 99%